A quadratic equation is an equation where the highest power of x is x2., so it is an equation of the form ax2 + bx + c = 0. There are various methods of solving quadratic equations, as shown below. NOTE: If x2 = 36, then x = +6 or -6 (since squaring either of these numbers will give 36). However, if we write ¥36, we usually mean +6 .

Completing the Square
9 and 25 can be written as 32 and 52 whereas 7 and 11 cannot be written as the square of another exact number. 9 and 25 are called perfect squares. Another example is (9/4) = (3/2)2. In a similar way, x2 + 2x + 1 = (x + 1)2. To make x2 + 6x into a perfect square, we add (62/4) = 9. The resulting expression, x2 + 6x + 9 = (x + 3)2 and so is a perfect square. The process of making something into a perfect square is known as completing the square. To complete the square in this way, we take the number before the x, square it, and divide it by 4. This technique can be used to solve quadratic equations, as demonstrated in the following example. Example Solve x2 - 6x + 2 = 0 by completing the square x2 - 6x = -2 [To complete the square on the LHS (left hand side), we must add 62/4 = 9. We must, of course, do this to the RHS also]. x2 - 6x + 9 = 7 (x - 3)2 = 7 [Now take the square root of each side] x - 3 = ±2.646 (the square root of 7 is +2.646 or -2.646) x = 5.646 or 0.354 Completing the square can also be used to find the maximum or minimum point on a graph. Example Find the minimum of the graph y = 3x2 - 6x - 3 . In this case, the x2 has a "3" in front of it, so we start by taking the three out: y = 3(x2 - 2x -1) . [This is the same, since multiplying it out gives 3x2 - 6x - 3] Now complete the square for the bit in the bracket: y = 3[(x - 1)2 - 2] Multiply out the big bracket: y = 3(x - 1)2 - 6 We are trying to find the minimum value that this graph can be. (x - 1)2 must be zero or positive, since squaring a number always gives a positive answer. So the minimum value will occur when (x - 1)2 = 0, which is when x = 1. When x = 1, y = -6 . So the minimum point is at (1, -6).

11 = -5 + 11 6 6 x = 1 or -2. The Quadratic Formula Let's complete the square in the general case: ax2 + bx + c Take out a factor of a: a [ x2 + (b/a)x + (c/a) ] a [ [x + (b/2a)]2 + (c/a) .(c/a) =b2 . and is known as the discriminant.4ac is therefore important.4ac 4a2 Now if we take the square root of both sides and simplify.4×3×(-8)) 6 = -5 ± ¥(25 + 96) 6 = -5 ± ¥ (121) 6 or -5 . . If b2 . This is actually derived by completing the square.4ac is less than zero.4ac is greater or equal to 0.8 = 0 x = -5 ± ¥( 52 . hence the graph of the curve will not cross the x-axis. The expression b2 . Some people don't like the method of completing the square to solve equations and an alternative is to use the quadratic formula.67 Quadratic Functions Since you only know how to take square roots of positive numbers.(b2/4a2) ] Hence if ax2 + bx + c = 0. we get the quadratic formula: Example Solve 3x2 + 5x . then there are no solutions. This means that there are no values of x giving a value of y of zero. the quadratic formula only gives real solutions if b2 .The minimum could also have been found by differentiation. [x + (b/2a) ]2 = (b2/4a2) .

There are a number of important rules of index numbers: a b a+b y y ×y =y Examples 24 × 28 = 212 54 × 5-2 = 52 a b a-b y y ÷y=y Examples 39 ÷ 34 = 35 72 ÷ 75 = 7-3 -b b y y = 1/y Examples 2-3 = 1/23 = 1/8 .4 If you do not understand the third line. factorising is probably the easiest way to solve the equation. Indices An index number is a number which is raised to a power. The power. also known as the index. therefore. remember that for (x . if b2 . Example Solve x2 + 2x . Factorising Sometimes.If b2 . In this case.2 = 0 or x + 4 = 0 x = 2 or x = . tells you how many times you have to multiply the number by itself.b/2a. so there is only one solution. The graph will only touch the x-axis at one point. 25 means that you have to multiply 2 by itself five times = 2×2×2×2×2 = 32. quadratic equations can be solved by factorising. then one of the two brackets must be zero. there will be 2 solutions to the equation and so the curve will cross the x-axis at 2 points.4ac > 0.8 = 0 (x .4ac = 0 then the quadratic formula says that x = .2)(x + 4) to equal zero.2)(x + 4) = 0 either x . For example. However.

Addition and subtraction of surds a¥b + c¥b = (a + c)¥b a¥b . This can be "tidied up" by multiplying the top and bottom of the fraction by a surd. (1 + ¥3) × (2 . . This is known as rationalising the denominator.2¥6 [The brackets are expanded as usual] Rationalising the denominator It is untidy to have a fraction which has a surd denominator. NB2: ¥a + ¥b is not the same as ¥(a + b) .¥8) = 2 .c¥b = (a . Example Rationalise the denominator of: a) 1 ¥2 .¥24 = 2 .¥8 + 2¥3 .c)¥b Examples 4¥7 . Multiplication and Division ¥ab = ¥a × ¥b ¥(a/b) = ¥a/¥b Examples ¥5 × ¥15 = ¥75 = ¥25 × ¥3 = 5¥3. 5¥2 + 8¥2 = 13¥2 NB1: 5¥2 + 3¥3 cannot be manipulated because the surds are different (one is ¥2 and one is ¥3).2¥2 + 2¥3 .2¥7 = 2¥7. since surds are irrational numbers and so you are changing the denominator from an irrational to a rational number.3-1 = 1/3 m/n y y = (n¥y)m Examples 161/2 = ¥16 = 4 82/3 = (3¥8)2 = 4 n m nm y (y ) = y Example 25 + 84 = 25 + (23)4 = 25 + 212 0 y y =1 Example 50 = 1 Surds Surds are numbers left in "square root form" (or "cube root form" etc).

Example Solve x2 + 3x + 2 > 0 Now. b) In situations like this. Now multiply the top and bottom of the fraction by this. Alternatively. to find the 4th term. (x + 2)(x + 1) > 0 when x < -2 or x > -1 . nth Term . we need to divide it up into a number of cases. Sequences In the sequence 2. therefore. When solving quadratic inequalities (inequalities with x2 in them).¥2 . The top will become ¥2 and the bottom will become 2 (¥2 times ¥2 = 2).b) 1 + 2 1 . it is important to remember that if you divide or multiply by a negative number.¥2 (1 . it is necessary to analyse the various cases to solve the inequality. the direction of the inequality is changed.2 -1 = -3(1 + ¥2) Inequalities When dealing with inequalities. 6. we know that (x + 2) is less than 0 and (x + 1) is less than zero. we can factorise the left hand side to get: (x + 2)(x + 1) > 0 To solve this.¥2 a) Multiply the top and bottom of the fraction by ¥2. you can draw the graph of x2 + 3x + 2 > 0 and look at where the graph lies above the x-axis. put n = 1 into the formula. based upon when the sign of one of the factors changes: x < -2 -2 < x < -1 x > -1 (x + 2) negative positive positive (x + 1) negative negative positive (x + 2)(x + 1) positive negative positive So when x < -2. From the table. the nth term = 2n.¥2)(1 + ¥2) 1 + ¥2 . Therefore (x + 2)(x + 1) > 0 (since negative times negative = positive). In this case. Doing this forms the conjugate of the denominator. Such sequences can be expressed in terms of the nth term of the sequence.. 4. look at the bottom of the fraction (the denominator) and change the sign (in this case change the minus into plus). 8. replace the n"s by 4"s: 4th term = 2 × 4 = 8. To find the 1st term.. Therefore: 1 + 2 = (1 + 2)(1 + ¥2) = 1 + ¥2 + 2 + 2¥2 = 3 + 3¥2 1 . for example. there is an obvious pattern. You should get the same answer. Drawing a table like this makes things easier. 10.

5. 10. Series The series of a sequence is the sum of the sequence to a certain number of terms. For example: 10. Notation The nth term of a sequence is sometimes written as Un . 12. 4. Un-1. . In many cases.. 0. consider the sequence: 2. For example... 9. there will probably be a three in the formula. other than to try different possibilities. The 5th term is therefore U5 = 25 + 1 = 26.625. the sum to 3 terms = S3 = 2 + 4 + 6 = 12. 26. Also. 16. Each term in the sequence is got by doubling the previous term.. 3. we give the first term.Trial and Error Example What is the nth term of the sequence 2. Sequences whose nth term approaches a finite number as n becomes larger are known as convergent sequences and the number to which the sequence converges is known as the limit of the sequence. 17. 10. written U1 = 2. Un = n² + 1 . Keep doing this until you get to 4. 1. is usually used to represent the sum of a sequence.. 5. since this is the number above the S. So to define the recurrence relation. For some sequences. 32. there is no easy way of working out the nth term of a sequence. 2. so try squaring n. converges (gets closer and closer) towards the limit zero. Tips: if the sequence is going up in threes (e. 8. Then we write: Un = 2(Un-1).). 4. Then replace r by 2 and write down what you get. This is ½n(n + 1). the triangular numbers formula often comes up. This is best explained using an example: This means replace the r in the expression by 1 and write down what you get. ? Let"s use trial and error (essentially guessing what we think will work): n = 1 2 3 4 5 n² = 1 4 9 16 25 n² + 1 = 2 5 10 17 26 This is the required sequence. . . So in the last example.. written S.25. Now add up all of the term that you have written down. 6. 6. So if the sequence is 2. . This just means that the nth term.. as above. square numbers will come up.. etc. Convergent Sequences Recurrence Relations This is where the next term of a sequence is defined using the previous term(s). Un is equal to 2 × the (n1)th term. . This sum is therefore equal to 3×1 + 3×2 + 3×3 + 3×4 = 3 + 6 + 9 + 12 = 30. 5. you have to give the first term. so the nth term is n² + 1.. It is often written as Sn. The Sigma Notation The Greek capital sigma.g. Then you give a formula to tell you how to work out the next term from the previous ones. 8.. . To define a recurrence relation.

The General Case n S Ur r=1 This is the general case.1)×2 ] = 10[ 2 + 19 × 2] = 10[ 40 ] = 400 The sum to n terms of an arithmetic progression Geometric Progressions A geometric progression is a sequence where each term is r times larger than the previous term. For example: 3. So for the sequence 3. is: a + (n .1) = 2n + 1. The terms in the sequence are said to increase by a common difference. In the above example. 7. 5. 9. 5. . 9.. . 7.. the first 20 odd numbers). (i. with first term a and common difference d. The nth term of a geometric progression. For the sequence Ur. 3.. This is given by: y Sn = ½ n [ 2a + (n ..1)d .3 S 3r + 2 r=1 This is equal to: (3×1 + 2) + (3×2 + 2) + (3×3 + 2) = 24 . It is derived as follows: The sum to n terms is given by: Sn = a + (a + d) + (a + 2d) + « + (a + (n 1)d) (1) If we write this out backwards. is: n-1 y ar . 5.. The nth term of this sequence is 2n + 1 . d. r is known as the common ratio of the sequence. is an arithmetic progression where d = 2.. the nth term of an arithmetic progression. where a is the first term and r is the common ratio. In general. 7. 2. Arithmetic Progressions An arithmetic progression is a sequence where each term is a certain number larger than the previous term. S20 = ½ (20) [ 2 × 1 + (20 . Ur = 3r + 2 and n = 3. 3. we get: (2) Sn = (a + (n 1)d) + (a + (n 2)d) + « + a Now let¶s add (1) and (2): 2Sn = [2a + (n 1)d] + [2a + (n 1)d] + « + [2a + (n 1)d] So Sn = ½ n [2a + (n 1)d] Example Sum the first 20 terms of the sequence: 1. which we already knew. up to and including n in turn for r in Ur.e. Un = 3 + 2(n . 11.1)d ] You may need to be able to prove this formula. 9.. this means the sum of the terms obtained by substituting in 1.

. So every time you add another term to the above sequence. 1 .5/0.. 16. 4. The nth term is therefore 2n-1 The sum of the first n terms of a geometric progression is: n y a(1 . in the following geometric progression. Find the 2 possible values for the fourth term of the geometric progression.r ) 1 r We can prove this as follows: Sn = a + ar + ar2 + « + arn-1 (1) Multiplying by r: rSn = ar + ar2 + « + arn (2) (1) (2) gives us: Sn(1 r) = a arn (since all the other terms cancel) And so we get the formula above if we divide through by 1 r . the result gets closer and closer to 1. if you keep adding together the terms of the sequence forever. .25) 1-2 = 2( 1 . This value is equal to: y a 1 r Example Find the sum to infinity of the following sequence: 1 . 16. 2. Example What is the sum of the first 5 terms of the following geometric progression: 2. the sum of the sequence as n tends to infinity approaches a value. 1 . 1 . 8. the sum to infinity is 0. The first term of the arithmetic progression is: a The second term is: a + d .For example. 1 . the first term is 1. 32 ? S5 = 2( 1 . Harder Example The first..5 = 1 . 8.32) -1 = 62 The sum of a geometric progression The sum to infinity of a geometric progression In geometric progressions where |r| < 1 (in other words where r is less than 1 and greater than 1). The third term of the arithmetic progression is 5. 4. In other words. second and fifth terms of an arithmetic progression are the first three terms of a geometric progression. a = 1/2 and r = 1/2 Therefore. . you will get a finite value. 2 4 8 16 32 64 Here. and the common ratio is 2: 1.. 1 .

. Therefore. so the geometric progression is 1. So a + 2d = 5 . In this case. 5.. a = 1 .. So the first term of the arithmetic progression (which is equal to the first term of the geometric progression) is either 5 or 1. a + d and a + 4d .When d = 2a. . r = 1 If d = 2a. We are told that the third term of the arithmetic progression is 5.. there is a common ratio. 5. a = 5 and when d = 2a. when d = 0.2a) = 0 therefore d = 0 or d = 2a The common ratio of the geometric progression. a = 5 and r = 1. when d = 0. r = 3a/a = 3 So the common ratio of the geometric progression is either 1 or 3 .. 27. and so the fourth term is 5. the geometric progression is 5.The fifth term is: a + 4d So the first three terms of the geometric progression are a. r = 3 and a = 1. 3. So: a + d = a + 4d a a+d (a + d)(a + d) = a(a + 4d) a² + 2ad + d² = a² + 4ad d² . Therefore. 5. 9. . if d = 0. is equal to (a + d)/a Therefore. and so the fourth term is 27. So the ratio of the second term to the first term is equal to the ratio of the third term to the second term. In a geometric progression. . r.2ad = 0 d(d .